Plasma neurofilament light chain protein is not increased in forensic psychiatric populations: a pilot study - Fernqvist, Anja; Alexiou, Eirini; Zetterberg, Henrik; Howner, Katarina; Nilsson, Thomas; Andiné, Peter (Frontiers in Psychiatry, 2023)
Introduction Neurofilament light chain protein (NfL) is a fluid biomarker of neural injury measurable in cerebrospinal fluid and blood. Patients with different neurodegenerative disorders and mild traumatic brain injury display elevated levels of NfL. However, so far, elevated levels of NfL have not been demonstrated in persons with psychiatric disorders. To our knowledge, the occurrence of NfL in the blood has not previously been studied in persons undergoing forensic psychiatric assessment or persons treated in forensic mental health services. Supposedly, these persons suffer from experiences and conditions with a higher risk of neural injury than other psychiatric patients. Methods In this pilot study, we investigated plasma levels of NfL in 20 persons undergoing forensic psychiatric assessment and 20 patients at a forensic psychiatric hospital. NfL values were compared with control groups of healthy individuals matched for age and sex. Results The prevalence of increased NfL in both forensic groups was low and did not differ compared with the controls. However, some persons undergoing forensic psychiatric assessment showed slightly elevated values. Discussion The slightly elevated values were observed in the group investigated closer in time to the index crime, when elevated NfL levels could be expected to be more prevalent due to acute conditions from the time of the offense. This gives reason to look further into this group.